If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2y = y + -6 + 3y Reorder the terms: 12 + -2y = -6 + y + 3y Combine like terms: y + 3y = 4y 12 + -2y = -6 + 4y Solving 12 + -2y = -6 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 12 + -2y + -4y = -6 + 4y + -4y Combine like terms: -2y + -4y = -6y 12 + -6y = -6 + 4y + -4y Combine like terms: 4y + -4y = 0 12 + -6y = -6 + 0 12 + -6y = -6 Add '-12' to each side of the equation. 12 + -12 + -6y = -6 + -12 Combine like terms: 12 + -12 = 0 0 + -6y = -6 + -12 -6y = -6 + -12 Combine like terms: -6 + -12 = -18 -6y = -18 Divide each side by '-6'. y = 3 Simplifying y = 3
| 5(9x+13)=7(4x+10) | | -35+7+12-18-1-16= | | 2(6x+14)=7(8x+12) | | 2(x+8)=5(x+11) | | 16=3x-X | | X=27+-1Y | | 6=3y+9 | | 2(x+6)=5(x+12) | | 20-/2=50 | | 1.5x=24 | | 1.5=24 | | 15=300 | | 3p^2-5p+2=y | | ln(X-7)-5=2 | | X+Y+10=37 | | 2/9t=36 | | 3B+4B=24 | | 16-3+-4+2-12+2= | | x^4-tx^2+16=0 | | 121^3/2 | | 10-2f=15-3f | | 5m+4m=27m | | 5y^2+7y-34=0 | | (7x-1)/5=x | | x^2-x/2-(x-4)^2/3≥0 | | 85=6k+5-(k+5) | | 85=6k+4-(k+5) | | 85=6k+4+(k+5) | | a-11=22 | | 85=6k+3-(2k+5) | | YGAF-YGAF= | | 6|4y-3|-2=16 |